Fretting fatigue of zinc coated low carbon steel EN H320 M - Ramalho, A. (2000)
The object of the present study was to investigate the influence of zinc coatings on steel sheets during fretting fatigue and fatigue tests. The influence of the fatigue stress range, normal pressure and amplitude of slip, on the fracture life was studied for both coated and uncoated EN H320 M steel. The wear produced by fretting was measured and compared with the fracture life evolution for different values of slip amplitude. The wear scars and the fracture surfaces were examined by scanning electron microscopy to identify the degradation mechanism. Although zinc films do not influence the fatigue life of the tested steel, when fretting is superposed on to a fatigue stress the coating markedly improves the fracture life.